Empirical determinants of relationship lending - Sahar Loukil; Anis Jarboui (Cogent Economics & Finance, 2016)
We study the determinants of the incidence of relationship lending. For our study, we combine established insights from the study of Elsas with empirical banking relationship lending literature. We relate loan contract and borrower characteristics to self-assessments of Tunisian banks with respect to the existence of close relationship. Using detailed loan contract information from Tunisian banks and a questionnaire addressed to loan officers, we report the first comprehensive evidence on the development of relationship lending. We find that access to information, the ability to influence the manager, and the solvency of the company are relevant factors. While the exclusivity and the duration of the relationship, classic measures of the existence of close ties with the bank, are not determining factors. So these proxy measures should be used with caution in future empirical works.
Keywords: 330; relationship lending; relational lender status; self-assessments; classic measures